European Banking Union structures and dynamics - José Alejandro Fernández Fernández (Cogent Economics & Finance, 2023)
This article begins with an analysis of banking flows in the euro zone, through a complex network, from 2006 to 2020. This analysis allows us to observe the topology of the network through different phases of the business cycle. It is obtained that there is greater fragmentation in the network that increases in three stages, with turning points in crises. In turn, the topological structure is less random and presents more capitalized subnetworks with less risk. As for the nodes of the network, Germany gives up the position of centrality in favor of France. The determinants of the links in the network are analyzed with Machine Learning, obtaining as push and pull bank variables solvency and bank income structure, respectively, and productivity as economic variable.
Keywords: G01; G15; G21; G28; C63; C6; 330; systemic risk; bank flows; bank integration; complex network